Methods, Thermodynamic Applications, and Habitat Implications of Physical and Spectral Properties of Hair and Haircoats in Cattle - Gebremedhin, Kifle G.; Fonseca, Vinicius D. F. C. [UNESP]; Maia, Alex S. C. [UNESP] (MDPI, 2023)
The physical properties (hair diameter, hair length, haircoat depth and haircoat density) and spectral properties (absorptivity, reflectivity, transmissivity) of the hair and haircoat of cattle are inputs to heat and moisture exchange between the skin surface and the surrounding environment, and thus play a critical role in body temperature regulation. Physical and spectral properties of haircoats also play an important role in protecting the skin against penetration of ultraviolet radiation. The focus of this review is to identify accurate and consistent measurement procedures of these properties. Additionally, the paper shows the utilization of the properties on heat exchange models and their implications on voluntary thermoregulation of cattle. To highlight the effects and benefits of haircoat color vis-à-vis solar radiation and its implication on ecological habitation, a brief explanation is provided using polar bears (white haircoat in a cold environment) and black goats in a hot desert environment.
Keywords: cattle haircoat; habitat implications of haircoat color; heat exchange; methods of measurement; physical and spectral properties; thermodynamic models